Rapamycin reverses ferroptosis by increasing autophagy in MPTP/MPP+-induced models of Parkinson's disease - Liu, Tongyu; Wang, Peihan; Yin, Huan; Wang, Xiangfei; Lv, Jing; Yuan, Jiang; Zhu, Jing; Wang, Yunfu (Neural regeneration research, 2023)
Parkinson's disease is a neurodegenerative disorder, and ferroptosis plays a significant role in the pathological mechanism underlying Parkinson's disease. Rapamycin, an autophagy inducer, has been shown to have neuroprotective effects in Parkinson's disease. However, the link between rapamycin and ferroptosis in Parkinson's disease is not entirely clear. In this study, rapamycin was administered to a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced Parkinson's disease mouse model and a 1-methyl-4-phenylpyridinium-induced Parkinson's disease PC12 cell model. The results showed that rapamycin improved the behavioral symptoms of Parkinson's disease model mice, reduced the loss of dopamine neurons in the substantia nigra pars compacta, and reduced the expression of ferroptosis-related indicators (glutathione peroxidase 4, recombinant solute carrier family 7, member 11, glutathione, malondialdehyde, and reactive oxygen species). In the Parkinson's disease cell model, rapamycin improved cell viability and reduced ferroptosis. The neuroprotective effect of rapamycin was attenuated by a ferroptosis inducer (methyl (1S,3R)-2-(2-chloroacetyl)-1-(4-methoxycarbonylphenyl)-1,3,4,9-tetrahyyridoindole-3-carboxylate) and an autophagy inhibitor (3-methyladenine). Inhibiting ferroptosis by activating autophagy may be an important mechanism by which rapamycin exerts its neuroprotective effects. Therefore, the regulation of ferroptosis and autophagy may provide a therapeutic target for drug treatments in Parkinson's disease.